Financial and Fiscal Programming Under Debt Rescheduling. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1989)
This paper reviews implications for financial and fiscal programming of different treatments of external debt rescheduling. Adjustment formulas are derived to ensure invariance of the macroeconomic outcome. An important consideration is the impact on the income position of the central bank. The results caution against the simple adjustment formulas sometimes applied. Even when defined on a 'falling due basis,' the size of the public sector deficit can be affected by the rescheduling treatment adopted. Under a properly defined aggregation between public sector deficit and income position of the central bank, the rescheduling treatment affects only the composition of the broader deficit.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet